Vaughan Glaser on Stage in Toronto 1921-1934 - Lawrence, Robert G. (Theatre Research in Canada / Recherches théâtrales au Canada, 1988)
The American actor and stock-company manager Vaughan Glaser settled in Toronto to operate an extraordinarily popular repertory company at the Uptown and Victoria theatres, September 1921-June 1928, with occasional appearances later. His carefully chosen comedies, musicals, pantomimes, melodramas and infrequent serious dramas contributed significantly to the great vogue for stock theatre in Toronto before radio, talking films, and the Depression brought it to an end. L’acteur américain et gérant de troupes résidentes, Vaughan Glaser, s’établit à Toronto entre septembre 1921 et juin 1928 et y anima une compagnie de répertoire particulièrement populaire, aux théâtres Uptown et Victoria. Son répertoire soigneusement choisi (comédies, comédies musicales, pantomimes, mélodrames et, plus rarement, pièces à caractère ’sérieux’) contribua de façon significative à la grande vogue de théâtre de répertoire à Toronto, avant que la radio, le cinéma parlant et la Crise y aient mis fin.